Simplify the expression.

4(5x2−3)−3(x2+1)
Responses

23x2−9
23 x squared minus 9

17x2−9
17 x squared minus 9

17x2−15
17 x squared minus 15

23x2−15

1 answer

Let's simplify the expression step by step:

Given expression:

\( 4(5x^2 - 3) - 3(x^2 + 1) \)

  1. Distribute \(4\) and \(-3\): \[ = 4 \cdot 5x^2 - 4 \cdot 3 - 3 \cdot x^2 - 3 \cdot 1 \] \[ = 20x^2 - 12 - 3x^2 - 3 \]

  2. Combine like terms:

    • Combine \(20x^2\) and \(-3x^2\): \[ = (20x^2 - 3x^2) - 12 - 3 \] \[ = 17x^2 - 12 - 3 \] \[ = 17x^2 - 15 \]

Thus, the simplified expression is:

17x² - 15

So the correct response is:

17 x squared minus 15.